Mengungkapkan Hubungan Antara Percaya Diri dan Kemampuan Pemecahan Masalah Matematis Siswa - Elmaini, Aldo; Wahyuni, Rika; Citroresmi P., Nindy (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to (1) determine the level of self-confidence among fourth-grade students at SDN 04 Singkawang in Mathematics lessons, (2) assess the level of mathematical problem-solving abilities of fourth-grade students at SDN 04 Singkawang, and (3) explore the relationship between self-confidence and mathematical problem-solving abilities among fourth-grade students at SDN 04 Singkawang. This research is quantitative in nature, employing a correlational study with a causal associative research design and using an asymmetrical relationship. The population of this study consists of all fourth-grade students, with the sample being the entire class, totaling 24 students. The results of the study are as follows: (1) The average self-confidence level of fourth-grade students at SDN 04 Singkawang is classified as